A Multi - Centered Study Of The Influence Of Hiv Infection On The Transmission Of Tuberculosis To Household Contacts Three States Of Malaysia. - Naing, Nyi Nyi; Mohammad, Zahiruddin; Abu Bakar, Mohd Hilmi; Salleh, Rosemi; Ahmad, Norita; Iyawo, Kuppusamy; Shaban, Hamidah; Simon, George Kutty; Joseph, Michael Stephen (2005)

(untitled)
A multi-centered cross-sectional study was carried out to examine tuberculin (Mantoux) response among household contacts of pulmonary TB (PTB) patients registered in Kota Bharu Hospital, Kelantan; Alor Setar Hospital Kedah and Institute of Respiratory Medicine, Kuala Lumpur from year 2000 through 2004.